Genome size variation among recent human isolates of Salmonella typhi - Thong, Kwai Lin; Puthucheary, S.D.; Pang, T. (Elsevier, 1997)
We performed genome size estimation of 17 recent human isolates of Salmonella typhi from geographically diverse regions using pulsed-field gel electrophoresis (PFGE) after digestion of chromosomal DNA with restriction endonucleases Xbal (5'-TCTAGA-3'), Avrll (5'-CCTAGG-3') and Spel (5'-ACTAGT-3'), and summation of the sizes of restriction fragments obtained. All 17 isolates had circular chromosomes, and genome sizes differed by as much as 959 kb, ranging from 3,964 to 4,923 kb (mean genome size = 4,528 kb). The data obtained confirm the usefulness of PFGE in studies of bacterial genome size and are in agreement with recent results indicating considerable genetic diversity and genomic plasticity of S. typhi. The variation in genome sizes noted may be relevant to the observed biological properties of this important human pathogen, including its virulence.